(untitled) (Research, Society and Development, 2024)
Objective: To verify the correlation between respiratory and peripheral muscle strength and functionality in hospitalized neurological patients. Methods: This is a cross-sectional study, evaluating 22 neurological patients hospitalized in a Regional Hospital, where a questionnaire was applied to collect personal data, and respiratory muscle strength was evaluated using the Manovacuometer, peripheral muscle strength using the Medical Research Council (MRC) and the dynamometer, and used the Functional Independence Measurement (MIF) scale to assess functional independence. Data normality was verified using the Shapiro-Wilk test, data were expressed as median and interquartile range, frequency and percentage. Kendall’s Tau B test was used for correlation analyses. The significance value adopted was p<0.05. Results: There was a reduction in respiratory muscle strength, which was below the expected level in all patients. Furthermore, there was a positive correlation between dynamometry with the MRC scale and with MIP and MEP. There was also a positive correlation between the MIF scale and the other instruments used. Conclusion: The instruments used correlated with each other, and showed that the dynamometer can indicate global muscle strength and serve as a simple and effective test to identify muscle weakness. Furthermore, the functionality of hospitalized patients was impacted by peripheral and respiratory muscle strength. Therefore, it is essential to carry out an assessment of patients undergoing hospitalization in order to screen for functional decline, and this assessment can be carried out safely, quickly and effectively with low-cost instruments.